The Effect of Investment Opportunity Set (IOS), Dividend and Tax Avoidance Policy on Company Value - irfani choiriyah sukriawan; Ratnasari, Fina (Universitas Pamulang, 2024)
This research aims to analyze the influence of the investment opportunity set (IOS), dividend policy and tax avoidance on the value of banking companies listed on the Indonesia Stock Exchange from 2018 to 2022. The object of this research is that the author chooses the financial reports of banking companies that report on the Indonesia Stock Exchange as the object. Using the criteria determined by the author, the data is processed to find a sample in this research which will be used as a reference in this research. The methodology used uses panel data regression and then tested using the classic assumption test where the results show that the investment opportunity set (IOS), dividend policy and tax avoidance together have an effect on company value, meaning that it shows that each independent variable in the research has a combined impact. on the dependent variable. Because companies with high value are considered to have strong performance, and investors are interested in investing in these organizations because they feel trusted. Keywords: Investment opportunity set (IOS), Dividend Policy, Tax avoidance